Fast Measurements of the Gas‐Liquid Diffusion Coefficient in the Gaussian Wake of a Spherical Bubble. Issue 5 (27th March 2015) - Dietrich, Nicolas; Francois, Jessica; Jimenez, Mélanie; Cockx, Arnaud; Guiraud, Pascal; Hébrard, Gilles
Abstract A fast method is proposed for determining the oxygen gas‐liquid diffusion coefficient from measurements of the fluorescence quenching behind a bubble. The approach consists of capturing pictures of the concentration field at micro‐scale in the laminar bubble wake. The Gaussian concentration profiles measured in the wake are demonstrated to be systematically equivalent to an instantaneous plane diffusion case. The approach permits to accurately evaluate the gas‐liquid diffusivity in a very short time of around one second.